ChemInform Abstract: Enantiodivergent Deprotonation/Acylation of α‐Amino Nitriles. Issue 19 (13th May 2014) - Sasaki, Michiko; Takegawa, Tomo; Sakamoto, Kunihiro; Kotomori, Yuri; Otani, Yuko; Ohwada, Tomohiko; Kawahata, Masatoshi; Yamaguchi, Kentaro; Takeda, Kei
Abstract Depending on the base used deprotonation and subsequent benzoylation of α‐ureidonitriles proceeds in a highly enantiodivergent manner to give enantiomeric benzoylated products without the need of any chiral catalyst.